Identification of Short and Long‐Lived Atmospheric Trace Gases From IASI Space Observations. Issue 5 (3rd March 2021) - De Longueville, Hélène; Clarisse, Lieven; Whitburn, Simon; Franco, Bruno; Bauduin, Sophie; Clerbaux, Cathy; Camy‐Peyret, Claude; Coheur, Pierre‐François
Abstract: In recent years, major progress has been made in measuring weakly absorbing atmospheric trace gases from high spectral resolution space observations. In this paper, we apply the so‐called whitening transformation on spectra of the Infrared Atmospheric Sounding Interferometer, and show that it allows removing most of the climatological background from spectra, leaving a residual that contains those spectral signatures that depart from normality. These can subsequently be attributed to changes in the abundance of trace species. This is illustrated for two diverging cases: (1) a biomass burning plume from the 2019/2020 Australian bushfires, leading to the unambiguous identification of nine reactive trace gases, including a first observation of glycolaldehyde; (2) spectra observed a decade apart, from which changes in eight long‐lived halogenated substances are identified; three of them never observed before by a nadir sounder. Plain Language Summary: In recent years, several techniques have been developed for the detection of gases present in very small quantities in the atmosphere, which has significantly improved our knowledge on atmospheric composition and chemistry. In this paper, we describe a powerful complementary technique that transforms atmospheric spectra to highlight and attribute the spectral signatures of different species. We apply it on spectra measured by the spaceborne Infrared Atmospheric Sounding Interferometer for two different cases: (1) a plume from the 2019/2020 Australian bushfires leading to the clear identification of nine rare gases including a first observation from space of glycolaldehyde; (2) spectra observed a decade apart, of which eight long‐lived halogenated substances were identified; three of them never observed before by a nadir sounder. The detection of these reactive and long‐lived trace gases is very promising for the monitoring of their temporal evolution and the attribution of their sources. Key Points: The whitening transformation allows analyzing anomalies in hyperspectral infrared spectra In a biomass burning plume we identify nine compounds including a first observation of glycolaldehyde On spectra observed a decade apart we identify atmospheric changes in eight long‐lived halocarbons